Policy Uncertainty and Manufacturing Investment: Evidence from U.S. State Elections - Cameron A. Shelton; Nathan Falk (Center for Economic Studies and ifo Institute (CESifo), 2016)
We estimate the effect of electorally induced policy uncertainty on investment in the manufacturing sector. Because state governors exercise considerable influence over legislation and considerable discretion over regulation and permitting, and because the policies relevant to business investment vary systematically by party, uncertainty over the partisan affiliation of the future governor is a source of political risk to firms considering business investment. More importantly, the lack of an incumbent in a race due to term limits raises uncertainty over the outcome, providing a convincing instrument that allows us to estimate causal effects. We find that, in a state with average partisan polarization, in the calendar year of a gubernatorial election, the elasticity of investment to the eventual margin of victory is 0.027. Both the significance and magnitude of this result are robust to various controls, measures, and estimators. Importantly, the investment decline is not reversed the following year. We show that own-state uncertainty is associated with a large and significant rise in neighboring states' investment, suggesting that rather than postponing investment to the future, the effect of policy uncertainty at the subnational level is to drive investment to alternative sites.
Keywords: D72; E02; E64; 330; policy uncertainty; investment; elections; US states